A Simplex-Optimized Chromatographic Separation of Phytoconstituents in Cardioprotective Polyherbal Formulation and Crude Drugs (Asian Journal of Pharmaceutics (AJP), 2022)
Aim: The study aims to develop and validate accurate, precise, and robust reverse phase high performance liquidchromatographic method for determination of phytoconstituents such as ascorbic acid, gallic acid, quercetin, andreserpine in polyherbal formulation and crude drugs. Materials and Methods: The adequate chromatographicseparation was accomplished on C18 column, 250 × 4.6 mm, 5 μmAgilent eclipse using mobile phase 0.05 Msodium dihydrogen phosphate buffer (pH-4 adjusted with 1% Orthophosphoric acid): Acetonitrile with properlyresolved gradient program. The flow rate was 1 ml/min, and the ultraviolet detection was monitored at 227 nm. Theretention time of ascorbic acid, gallic acid quercetin and reserpine was found to be 3.44 min, 5.26 min, 10.02 minand 13.24 min, respectively. The method was validated as a final verification of method development concerningprecision, linearity, accuracy, sensitivity and robustness as per International Council for Harmonization (ICH)guideline Q2 (R1). Results and Discussion: A method is considered to be linear as the correlation coefficient wasfound to be within acceptance criteria. The detector response was linear in the range of 50–250 μg/ml Ascorbicacid, 100-300 μg/ml Gallic acid, 100-300 μg/ml, Quercetin and 50–250 μg/ml Reserpine. The % RSD of peakarea response due to Ascorbic acid, Quercetin, Reserpine and Gallic acid in five replicate injections of standardsolution was to be less than 2.0%, and system suitability parameters were passed. Conclusion: The proposedmethod was effectively applied for the simultaneous estimation of Ascorbic acid, Gallic acid, Quercetin andReserpine in Polyherbal formulation and in crude drugs.